2002
DOI: 10.1183/09031936.02.00268002
|View full text |Cite
|
Sign up to set email alerts
|

Sequential genotyping ofPseudomonas aeruginosafrom upper and lower airways of cystic fibrosis patients

Abstract: A controversy exists concerning the adequate specimen to characterise colonisation of cystic fibrosis (CF) airways by Pseudomonas aeruginosa. Oropharyngeal, sputum and bronchoalveolar lavage samples were evaluated from 38 stable CF patients for the detection of P. aeruginosa, genetically different isolates within the same host and longitudinal variations in the genotype during repeated examinations.Bacterial isolates were typed by pulsed-field gel electrophoresis of deoxyribonucleic acid macrorestriction fragm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
41
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 21 publications
4
41
0
Order By: Relevance
“…This is consistent with several previous longitudinal studies of CF patients (Burns et al, 2001;Ener et al, 2001;Fegan et al, 1991;Jelsbak et al, 2007;Jung et al, 2002;Mahenthiralingam et al, 1996). A previous study using the AT system to genotype multiple isolates of P. aeruginosa from CF patients also reported evidence of strain replacement, the failure of some strains to establish infection, and genetic variations amongst isolates of the same AT genotype (Jelsbak et al, 2007).…”
supporting
confidence: 93%
“…This is consistent with several previous longitudinal studies of CF patients (Burns et al, 2001;Ener et al, 2001;Fegan et al, 1991;Jelsbak et al, 2007;Jung et al, 2002;Mahenthiralingam et al, 1996). A previous study using the AT system to genotype multiple isolates of P. aeruginosa from CF patients also reported evidence of strain replacement, the failure of some strains to establish infection, and genetic variations amongst isolates of the same AT genotype (Jelsbak et al, 2007).…”
supporting
confidence: 93%
“…Several other studies also have reported temporal variation in CF P. aeruginosa isolate PFGE band patterns (22,32,38) and point to evidence of within-host evolution. In contrast, MLST, as shown here and elsewhere (43), reveals evidence of long-term stability.…”
Section: Discussionmentioning
confidence: 96%
“…By far the most widely used sample in productive patients is spontaneously expectorated sputum (SES). SES samples have been shown to have high concordance with bronchoalveolar lavage samples in microbial terms (17), with the impact of contamination during the process of expectoration being minimal (31). Further, the use of SES samples has significant advantages in that they can be collected with a short notice period and with high frequency.…”
mentioning
confidence: 99%